Complications, Symptoms, Presurgical Predictors in Patients With Chronic Hypoparathyroidism: A Systematic Review. (14th November 2022) - Yao, Liang; Hui, Xu; Li, Meixuan; Li, Jing; Ahmed, Muhammad Muneeb; Lin, Clement; Kandi, Maryam; Sreekanta, Ashwini; Makhdami, Nima; Tamilselvan, Divya; Ali, Dalal S.; Dandurand, Karel; et al.
ABSTRACT: The complications and symptoms of hypoparathyroidism remain incompletely defined. Measuring serum parathyroid hormone (PTH) and calcium levels early after total thyroidectomy may predict the development of chronic hypoparathyroidism. The study aimed (i) to identify symptoms and complications associated with chronic hypoparathyroidism and determine the prevalence of those symptoms and complications (Part I), and (ii) to examine the utility of early postoperative measurements of PTH and calcium in predicting chronic hypoparathyroidism (Part II). We searched Medline, Medline In‐Process, EMBASE, and Cochrane CENTRAL to identify complications and symptoms associated with chronic hypoparathyroidism. We used two predefined criteria (at least three studies reported the complication and symptom and had statistically significantly greater pooled relative estimates). To estimate prevalence, we used the median and interquartile range (IQR) of the studies reporting complications and symptoms. For testing the predictive values of early postoperative measurements of PTH and calcium, we used a bivariate model to perform diagnostic test meta‐analysis. In Part I, the 93 eligible studies enrolled a total of 18, 973 patients and reported on 170 complications and symptoms. We identified nine most common complications or symptoms probably associated with chronic hypoparathyroidism. The complications or symptoms and the prevalence are as follows: nephrocalcinosis/nephrolithiasis (median prevalence among all studies 15%), renal insufficiency (12%), cataract (17%), seizures (11%), arrhythmia (7%), ischemic heart disease (7%), depression (9%), infection (11%), and all‐cause mortality (6%). In Part II, 18 studies with 4325 patients proved eligible. For PTH measurement, regarding the posttest probability, PTH values above 10 pg/mL 12–24 hours postsurgery virtually exclude chronic hypoparathyroidism irrespective of pretest probability (100%). When PTH values are below 10 pg/mL, posttest probabilities range from 3% to 64%. Nine complications and symptoms are probably associated with chronic hypoparathyroidism. A PTH value above a threshold of 10 pg/mL 12–24 hours after total thyroidectomy is a strong predictor that the patients will not develop chronic hypoparathyroidism. Patients with PTH values below the threshold need careful monitoring as some will develop chronic hypoparathyroidism. © 2022 American Society for Bone and Mineral Research (ASBMR).